Exploring the link between extraversion tendencies and ESL proficiency - Ahmad Bukhari, Nurul Iman; Tengku Abd Aziz, Tengku Mohd Farid; Mohd Saad, Muhammad Luqman Ibnul Hakim; Ismail, Lilliati; Abdul Razak, Amanina (Nun Gemilang, 2023)
This study investigates the relationship between extraversion personality traits and language performance among pre-university students in Malaysia. English proficiency plays a crucial role in various domains, including education and the workforce, in the multicultural and multilingual context of Malaysia. English is especially critical for tertiary education where most universities in Malaysia use English in the classroom. However, extraversion indicating extrovert and introvert personality may affect student performance in the ESL classroom. The study sample consists of 226 pre-university students studying English at tertiary level at Form 6 and matriculation institutions. The research utilises a Student Demographic Questionnaire, which collects information on the participants' grades in the English examination they took at the end of their secondary school studies (Sijil Pelajaran Malaysia), and the Eysenck Personality Questionnaire to assess extraversion traits. One-Way Analysis of Variance (ANOVA) was employed to analyse the data and determine if significant differences exist among different levels of English proficiency. The findings indicate that there is no significant difference in language proficiency among students with varying levels of achievement in English at the SPM level. These results suggest that students of different extraversion traits have equal abilities in language performance among students in Malaysia. The research contributes to the understanding of factors influencing language proficiency and provides insights for language educators and policymakers to develop effective language learning strategies and interventions. Future research could explore additional factors that may influence language performance among students in Malaysia to further enhance language education in the country.